Writing University History in Great Britain, from the 1960s to the Present - Anderson, Robert (CIAN-Revista de Historia de las Universidades, 2017)
This article surveys the writing of university history in Great Britain since the 1960s, when its modern foundations were laid through the impact of the new social history. Specific features of the British case include the separate university histories of England and Scotland, which have conditioned the kind of history that can be written; the duopoly of Oxford and Cambridge before the nineteenth century; and the growth of a national system by the accretion of new strata, with their own distinct histories. The 1980s and 1990s were marked by large collective projects, at Oxford, Cambridge and Aberdeen. The tradition of writing histories of individual institutions (including Oxford and Cambridge colleges) has continued, though today on a more scholarly basis than in the past. Among the general themes investigated in recent years have been relations between universities and industry, the growth of state intervention and finance, universities and elites, links with the British empire, the development of disciplines and curricula, student life, the growth of women’s higher education, and university architecture. University historians have been influenced by the historiographical turn from social to cultural history. But while individual research flourishes, the history of universities has not become a formal subdiscipline in Britain, and the article considers why this is so.
Keywords: Great Britain; Scotland; universities; history of universities; social history